Séparation et Dosage d’Anions Inorganiques dans les Eaux Naturelles par Chromatographie Ionique et Détection Conductimétrique - S. Dogan; W. Hærdi (CHIMIA)
The determination of inorganic anions in natural waters often requires sensitive tools as they are present at trace levels. This can however be achieved by means of high performance ion-exchange chromatography. In this work the possibility of using a system without a suppressor column for its analysis has been described. The sensitivity of this technique is chiefly dependent on the relative conductance of the anion with respect to the eluant. The detection limit of the method under optimal pH and eluant concentration is of the order of 0.1-0.2 ppm (Injection volume = 0.2 ml) for most of the anions (HCOO-, Cl-, NO2-, Br-, NO3-, SO42-, S2O32-) except H2PO4- and HCO3- (4-5 ppm). This limit can be improved further by a factor of 10-50 depending on the injection volume using a preconcentration column. Application of this technique to inorganic anion analysis in rain water, various mineral waters, domestic water supply, lake waters and interstial waters (sediments) has been reported.